2019
DOI: 10.12659/ajcr.913522
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection Masquerading as Coronary Artery Stenosis in a Young Patient

Abstract: Patient: Male, 34Final Diagnosis: Spontaneous coronary artery dissectionSymptoms: Chest painMedication: —Clinical Procedure: —Specialty: CardiologyObjective:Rare diseaseBackground:Spontaneous coronary artery dissection (SCAD) is primarily found in females. SCAD can have many precipitating factors such as exercise, trauma, pregnancy, drugs, and connective tissue disease. Prognosis is poor for left main stem, left anterior descending (LAD) artery, and multivessel involvement, especially for females.Case Report:W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(27 reference statements)
0
0
0
1
Order By: Relevance
“…The incidence and the true prevalence of SCAD remain uncertain because it is frequently undiagnosed, but studies have shown the estimated prevalence of SCAD is as high as 2.1% of all patients presenting with ACS [6]. It is most commonly seen in healthy younger women (87%-95% of SCAD) with a mean age of presentation between 44 and 55 years [2,6,7]. SCAD most commonly occurs in patients with few or no traditional cardiovascular risk factors [8,9].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence and the true prevalence of SCAD remain uncertain because it is frequently undiagnosed, but studies have shown the estimated prevalence of SCAD is as high as 2.1% of all patients presenting with ACS [6]. It is most commonly seen in healthy younger women (87%-95% of SCAD) with a mean age of presentation between 44 and 55 years [2,6,7]. SCAD most commonly occurs in patients with few or no traditional cardiovascular risk factors [8,9].…”
Section: Epidemiologymentioning
confidence: 99%
“…The second mechanism presents as compression due to hematoma and needs imaging to differentiate from atherosclerotic stenosis [7]. Both mechanisms develop a false channel in the middle layer, which causes obstruction or compression of the vessel, leading to decreased blood flow to the heart and causing myocardial ischemia [1,2].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Опубликован случай расслоения верхней брыжеечной артерии, проявлявшийся абдоминальной болью [44]. Случаи спонтанного расслоения коронарных артерий, которые наблюдаются главным образом у женщин, могут быть не распознаны при обычной ангиографии как причина стеноза, фатальны и могут приводить к развитию инфаркта миокарда и внезапной сердечной смерти [45,46].…”
Section: васкулопатииunclassified